Increased expression of inactive rhomboid protein 2 in circulating monocytes after acute myocardial infarction. (11th May 2021) - Van Dijck, P; Hannemann, C; Dreger, H; Stangl, K; Ludwig, A; Hewing, B
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Deutsche Forschungsgemeinschaft (DFG; Sachbeihilfe HE6092/2) DGK (Deutsche Gesellschaft für Kardiologie) Otto-Hess-Promotionsstipendium Purpose: Tumor necrosis factor-alpha (TNF-α) levels in the blood increase in the course of an acute myocardial infarction (AMI) and TNF-α is involved in the impaired recovery of myocardial function following AMI. The interaction of inactive rhomboid protein 2 (iRhom2) with the TNF-α converting enzyme (TACE) is required for the proper shedding of TNF-α from the cell surface of immune cells. We hypothesized, that iRhom2 expression increases in circulating monocytes of patients following AMI.  Methods: Circulating monocytes were MACS-sorted from peripheral blood of 50 patients with AMI (NSTEMI, n = 16; STEMI n = 34) at the day of admission (day 1) and 3 days after admission. 50 patients with chronic coronary syndrome (CCS) were recruited as control. mRNA was isolated from sorted monocytes and expression levels of iRhom2, TACE and TNF-α were evaluated by real-time RT-PCR. TNF-α protein levels were assessed in the serum. Levels of circulating classical, intermediate and non-classical monocyte subsets were determined by flow cytometry.  Results: There was a significant increase of iRhom2 mRNA expression levels in monocytes (by 14%, p = 0.012), levels of circulating intermediate monocytes (p < 0.001), and TNF-α serum levels (p < 0.001) at day 3 following AMI compared to day 1 reaching levels similar to those observed in CCS patients. In contrast, TNF-α and TACE mRNA expression in circulating monocytes did not differ between day 1 and 3 following AMI. iRhom2 mRNA expression in monocytes on day 3 following AMI correlated with TACE mRNA expression in monocytes (r = 0.72, p < 0.001), TNF-α serum levels (r = 0.33, p = 0.019), and levels of circulating intermediate monocytes (r = 0.37, p = 0.009). Conclusions: Following AMI, iRhom2 expression in circulating monocytes increases in parallel to serum levels of TNF-α and levels of circulating intermediate monocytes. These findings suggest that iRhom2 contributes to inflammation following AMI and thus may serve as a potential therapeutic target.